Impact of Ge content on the electrochemical performance of Germanium Oxide/Germanium/ reduced graphene (GeO2/Ge/r-GO) hybrid composite anodes for lithium-ion batteries - Christian Randell Arro (17128855) (2022)
Hybrid composites between Germanium (Ge) and carbonaceous materials have been extensively studied due to the carbonaceous’ component’s ability to mitigate the intrinsic problems pertaining to Ge-based anodes. The mitigation of reduced cycling ability and rate capability allows for the unhindered benefit of higher capacities in Ge-carbonaceous composite anodes. Here, the effect of different Ge mass loading on electrochemical performance is studied on a GeO2/Ge/r-GO composite made using controlled microwave radiation of ball-milled Ge and sonicated dispersion of graphene Oxide (GO) as a lithium battery anode. The composite anode at Ge 25% showed greatest cycling retention with 91% after 100 cycles and an average specific capacity of 300 mAh/g (1600 mAh/g Ge). At 75% Ge mass loading the anode suffered with limited cycling retention of 57.5% at the cost of greater specific capacities. The composite at 50% Ge attained advantageous characteristics of both composites with a stable cycling performance of 71.4% after 50 cycles and an average specific capacity of 400 mAh/g (1067 mAh/g Ge, all conducted at a current density of 100 mA/g). A positive linear correlation is revealed for increasing Ge mass loadings and specific capacities in Ge-carbonaceous as anode materials. Other Information Published in: Materials Today Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mtcomm.2022.103151